The Inscription in the 'Du khang of Dgung 'phur Monastery, Spu rang (Mnga' ris) - Tropper, Kurt (Verlag der Österreichischen Akademie der Wissenschaften, 2016)
This study essentially provides the edition and annotated translation of a historical inscription in the assembly hall of Dgung 'phur Monastery in Spu rang (Mnga' ris, Western Tibet). The inscription deals with religious and political events in the history of Western Tibet up to the beginning of the 17th century. The introductory part of the study includes a description of the inscription's general characteristics, a summary of its contents, an enquiry into its date and a discussion of the magistrate Mgon po skyabs, whom the inscription identifies as the "founder" of Dgung 'phur.